Pengaruh Kepemimpinan Kepala Sekolah dan Kualitas Mengajar Guru terhadap Prestasi Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan Kelas XI SMA Negeri 1 Siantar T.P. 2022/2023 - Rindu Sinaga; Daulat Nathanael Banjarnahor; Sepriandison Saragih; Wesly Nababan (Journal on Education, 2023)
This study aims to determine whether there is an influence of the principal's leadership and the quality of teacher learning on the learning achievement of class XI students of SMA Negeri 1 Siantar in the 2022/2023 academic year. The population and sample in this study were 47 0 students of class XI. Obtaining data on the leadership of school principals and the teaching quality of teachers used a questionnaire as a data collection tool and what was used was a closed questionnaire which was arranged in a structured manner where the question items were followed by answers consisting of four choices. The questionnaire research instrument was assessed through validity and reliability tests. All data from the two variables above were first tested whether they were normally distributed or not by using the fit test or chi square test and it turned out that the two variables were normally distributed. The next step is to test the hypothesis by calculating the linear regression equation, namely Y over X1 is = 14.59 + 1.17 X1 means that between variables X1 is linear with Y and Y over X2 is = 15.70 + 0.11 X2 means between variables X2 is linear with Y and Y for X1 and X2 is = 90.96 + 1.17X1 +0.11 X2 means that between the variables X1 and X2 is linear with Y. Based on the hypothesis test, namely the significance test (t test) by rejecting H0 and If You receive H1, you will get: The Influence of the Principal's Leadership on Student Learning Achievement in PKN Class XI Subject at SMA Negeri 1 Siantar Academic Year 2022/2023. The Influence of Teacher Teaching Quality on Student Learning Achievement in PKN Subjects Class XI SMA Negeri 1 Siantar Academic Year 2022/2023. The Influence of the Principal's Leadership and the Quality of Teacher Learning Together on the Learning Achievement of Class XI Students in PKN Subject at SMA Negeri 1 Siantar for the Academic Year 2022/2023.